Evaluation of SAPA WARGA Application System and User Satisfaction: Public Service Technology Management Perspective Based on PIECES Framework - Fauzi, Irwan Maulana; Nugroho, Ario Adi; Khoirunisa, Alfiah (JURNAL SISFOTEK GLOBAL, 2025)
The utilization of technology in public services continues to evolve to enhance efficiency, transparency, and service quality for society. However, the implementation of technology in the public sector still faces various challenges, such as human resource readiness, infrastructure, and resistance to change. This study aims to evaluate the SAPA WARGA application using the PIECES framework, which includes aspects of Performance, Information, Economy, Control, Efficiency, and Service. The application is used by the West Java Provincial Government to improve public services by providing convenience for the public in reporting complaints, conveying aspirations, and accessing information related to public services. The survey results showed that the majority of respondents were satisfied with the application's performance, customer support, and vehicle tax due reminder feature. However, several areas still require improvement, such as application speed, information consistency, and response to user complaints.